Problems of legal regulation of the activities of the housing co-operative in the field of management of an apartment house (Путеводитель предпринимателя)
In the article are analyzed the problems of the legal regulation of the housing co-operative in the field of management of an apartment house, in particular, examines the possibility of transmission of the management of real property of the cooperative company of proprietors of habitation or the managing organization.